2021
DOI: 10.1186/s13045-021-01051-z
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of RUNX1 transcription factor activity by a CBFA2T3-mimicking peptide: application to B cell precursor acute lymphoblastic leukemia

Abstract: Background B Cell Precursor Acute Lymphoblastic Leukemia (BCP-ALL) is the most common pediatric cancer. Identifying key players involved in proliferation of BCP-ALL cells is crucial to propose new therapeutic targets. Runt Related Transcription Factor 1 (RUNX1) and Core-Binding Factor Runt Domain Alpha Subunit 2 Translocated To 3 (CBFA2T3, ETO2, MTG16) are master regulators of hematopoiesis and are implicated in leukemia. Methods We worked with BCP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 56 publications
0
11
0
Order By: Relevance
“…The study undertaken by Goyama et al indicated a significant link between the function of the selected genes and leukemic cell survival [ 28 ]. The RUNX1 gene is frequently deregulated in childhood B-cell precursor acute lymphoblastic leukemia (BCP-ALL), where the ETV6-RUNX1 translocation causes an overexpression of the RUNX1 gene [ 29 , 30 , 31 ], on the other hand this gene can also be aberrantly expressed in T-ALL cases, where it is reported to be oncogenic in the T-cell lineage and to cause lymphoma in mice [ 32 ]. Despite the similar disease symptoms to childhood leukemia, the adult ALL seems to be a different entity with an altered genetic background and the specific expression pattern is still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…The study undertaken by Goyama et al indicated a significant link between the function of the selected genes and leukemic cell survival [ 28 ]. The RUNX1 gene is frequently deregulated in childhood B-cell precursor acute lymphoblastic leukemia (BCP-ALL), where the ETV6-RUNX1 translocation causes an overexpression of the RUNX1 gene [ 29 , 30 , 31 ], on the other hand this gene can also be aberrantly expressed in T-ALL cases, where it is reported to be oncogenic in the T-cell lineage and to cause lymphoma in mice [ 32 ]. Despite the similar disease symptoms to childhood leukemia, the adult ALL seems to be a different entity with an altered genetic background and the specific expression pattern is still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Since RUNX1 and CBFA2T3 are upregulated in ETV6-RUNX1 B cell precursor ALL (BCP-ALL) [288], it suggests that RUNX1 and CBFA2T3 may act as a driver loop in BCP-ALL. Indeed, use of a truncated CBFA2T3 protein significantly inhibited RUNX1 activity and reduced BCP-ALL cell proliferation [287].…”
Section: Exploiting Enhancers By Deregulated Transcription Factorsmentioning
confidence: 99%
“…RUNX1 also interacts with CBFA2T3 which enhances its transcriptional activity. They act in a self-activation loop, as RUNX1 binds its own promoter and the CBFA2T3 enhancer located 2 kb upstream of the CBFA2T3 promoter [287]. Since RUNX1 and CBFA2T3 are upregulated in ETV6-RUNX1 B cell precursor ALL (BCP-ALL) [288], it suggests that RUNX1 and CBFA2T3 may act as a driver loop in BCP-ALL.…”
Section: Exploiting Enhancers By Deregulated Transcription Factorsmentioning
confidence: 99%
“…The CBFA2T3 gene, located on chromosome 16q24.3, is a member of the ETO gene family and an important regulator in hematopoietic progenitor cell proliferation, erythropoiesis, and leukemia stem cell transformation [6-8]. CBFA2T3 encodes a protein that contains four evolutionary conserved nervy homology regions (NHR 1-4), among which the NHR2 domain can interact with hematopoiesis-related transcription factor RUNX1, promoting acute lymphoblastic leukemia proliferation [2].…”
Section: Introductionmentioning
confidence: 99%